Tephroseris integrifolia subsp. integrifolia - Jarvis, Charlie (Linnaean Society of London in association with the Natural History Museum, 2007)
Cineraria alpina (Linnaeus) Linnaeus var. integrifolia (Linnaeus) Linnaeus, Species Plantarum , ed. 2, 2: 1243. 1763. ["Habitat in Alpibus Pyrenaicis, Helveticis, Austriacis, Sibiricis."] Sp. Pl. 2: 925 (1753). RCN: 6366. Basionym: Othonna integrifolia L. (1753). Type not designated. Original material: as basionym. Current name: Tephroseris integrifolia (L.) Holub subsp. integrifolia (Asteraceae). Published as part of Jarvis, Charlie, 2007, Chapter 7: Linnaean Plant Names and their Types (part C), pp. 370-473 in Order out of Chaos. Linnaean Plant Types and their Types, London :Linnaean Society of London in association with the Natural History Museum on page 417, DOI: 10.5281/zenodo.291971